Occupation and renal cell cancer in Central and Eastern Europe. Issue 1 (7th September 2009) - Heck, J E; Charbotel, B; Moore, L E; Karami, S; Zaridze, D G; Matveev, V; Janout, V; Kollárová, H; Foretova, L; Bencko, V; Szeszenia-Dabrowska, N; Lissowska, J; et al.
Abstract : Objective: Central and Eastern Europe has among the highest rates of renal cell cancer worldwide. Few studies have been conducted in these areas to investigate the possible role of occupational exposures in renal cell cancer aetiology. The purpose of this study was to examine the association of renal cell cancer with employment in specific occupations and industries. Methods: From 1999 to 2003, we conducted a hospital-based case-control study in seven areas of the Czech Republic, Poland, Romania and Russia. A detailed occupational history was collected from renal cell cancer cases and controls, together with information on potential confounders. Odds ratios (ORs) and 95% CI of cancer risk were calculated for having ever been employed in selected jobs and industries, with follow-up analyses examining duration of employment. Results: A total of 992 histologically confirmed incident renal cell cancer cases and 1459 controls were included in the analysis. An increased risk of renal cell cancer was observed for workers in agricultural labour and animal husbandry (OR 1.43; 95% CI 1.05 to 1.93), particularly among women employed as general farm workers (OR 2.73; 95% CI 1.05 to 7.13). Risk gradients for agricultural work increased with longer employment. An overall increased risk of renal cell cancer was seen among architects and engineers (OR 1.89; 95% CI 1.35 to 2.65), and mechanical engineers (OR 1.71; 95% CI 1.03 to 2.84). Conclusions: Our data suggest an association between renal cell cancer and agricultural work, particularly among female workers.